Eva Creamery Sdn. Bhd. / Rabaah Seli ... [et al.] - Seli, Rabaah; Saad, Khadijah; Ibrahim, Azian; Mat Hassan, Mastura; Md Hashim, Sabrina (2001)
Our company main activity in run this business is to produce and distribute ice cream product in north area Kedah and Perlis. Each of us has our owned skill and part in the business. As we know, Nowdays most ice-cream manufacturer 1st come from non Bumiputera. No one from Bumiputera's ore try to enter in this business field. Five of us are very proud to be the 1st Bumiputera's company in handling and making ice-cream manufacturing in Malaysia especially in north area. We try to produce many types of ice-cream based on taste, shape and others. Our ice-cream product consist of stick ice-cream, cones ice-cream, cup ice-cream and cream line ice-cream. We already fixed the price of our product at a competitive price as we regarded as a new company in the industry . Our business was located at Alor Setar, Kedah.